Navigating large scale ocean science in a Pacific small island developing state - Claassens, Louw; Hernandez, Christina; Biondi, Piera; Jaskiel, Jacob; Karanassos, Christina; Mesengei, McQuinnley; Nestor, Victor; Otto, Ikelau; Renguul, H.; Rotjan, Randi; Sartori, Greta; Tatebe, Lyvonsky (Commonwealth Scientific and Industrial Research Organisation, 2024)
Context. In pursuit of protecting 30% of the ocean by 2030, large scale marine protected areas (LSMPAs) are rapidly increasing, especially in small island developing states (SIDS). Many SIDS have limited offshore research expertise or capacity to evaluate the efficacy of LSMPAs. The offshore Palau National Marine Sanctuary (PNMS) necessitated the Republic of Palau to develop its offshore research ability aimed at supporting science-based management. Owing to Palau’s important tuna fishery, investigating tuna reproductive biology in the PNMS was prioritized as a first step in evaluating the protective significance of the PNMS for tuna. Aims. The aim of this study was to develop a useful and practical platform to conduct large scale ocean research within the context of SIDS. Methods. A platform to conduct offshore research was developed. Reproductive histology and the presence and abundance of larvae were used to investigate tuna reproductive biology in the PNMS. Key results. Most tunas sampled were mature, with 3 of the 59 sampled fish actively spawning. Twenty two tuna larvae were collected across five offshore sites, and modeling results suggest larvae originated from these sites. Conclusions. Findings suggest tuna spawn, to some extent, within the PNMS, and the PNMS provides local protection to tuna populations during this time. A research platform with five steps for developing, undertaking and understanding offshore research in SIDS was developed. Challenges and tips experienced are also detailed. Implications. This platform can support the ever-increasing demand for offshore research in small island, large ocean states with limited resources and expertise.